2021
DOI: 10.1101/2021.07.21.21260953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of transcranial direct current stimulation (tDCS) combined with cognitive training on EEG spectral power in adolescent boys with ADHD: a double-blind, randomised, sham-controlled trial

Abstract: Transcranial direct current stimulation (tDCS) is a possible neurotherapeutic alternative to psychostimulants in Attention-Deficit/Hyperactivity Disorder (ADHD). However, very little is known regarding the mechanisms of action of tDCS in children and adolescents with ADHD. We conducted the first multi-session, sham-controlled study of anodal tDCS over right inferior frontal cortex (rIFC), a consistently under-functioning region in ADHD, combined with cognitive training (CT) in 50 children/adolescents with ADHD… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…The study found that both groups improved in clinical symptoms and cognitive functions, but the improvement in the real versus sham tDCS in primary and secondary clinical outcome measures was significantly less pronounced [162] . Groups did not differ in a large battery of executive function cognitive outcome measures [162] nor in EEG measures within a smaller subsample of data collected from 26 participants only [163] . Furthermore, the real tDCS group had worse adverse effects related to mood, sleep and appetite immediately after stimulation [163].…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 83%
See 1 more Smart Citation
“…The study found that both groups improved in clinical symptoms and cognitive functions, but the improvement in the real versus sham tDCS in primary and secondary clinical outcome measures was significantly less pronounced [162] . Groups did not differ in a large battery of executive function cognitive outcome measures [162] nor in EEG measures within a smaller subsample of data collected from 26 participants only [163] . Furthermore, the real tDCS group had worse adverse effects related to mood, sleep and appetite immediately after stimulation [163].…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 83%
“…Groups did not differ in a large battery of executive function cognitive outcome measures [162] nor in EEG measures within a smaller subsample of data collected from 26 participants only [163] . Furthermore, the real tDCS group had worse adverse effects related to mood, sleep and appetite immediately after stimulation [163].…”
Section: Transcranial Direct Current Stimulation (Tdcs)mentioning
confidence: 83%